The role of sema4D in vasculogenic mimicry formation in non‐small cell lung cancer and the underlying mechanisms. Issue 9 (6th December 2018) - Xia, Yun; Cai, Xian‐Yi; Fan, Ji‐Quan; Zhang, Li‐Ling; Ren, Jing‐Hua; Li, Zhen‐Yu; Zhang, Rui‐Guang; Zhu, Fang; Wu, Gang
Abstract : Vasculogenic mimicry (VM) is a special vascular pattern in malignant tumors, which is composed of highly aggressive tumor cells. This tumor cell‐mediated blood supply pattern is closely associated with a poor prognosis in cancer patients. The interaction of axon guidance factor Sema4D and its high affinity receptor plexinB1 could activate small GTPase RhoA and its downstream ROCKs; this process has an active role in the migration of endothelial cells and tumor angiogenesis. Here, we have begun to uncover the role of this pathway in VM formation in non‐small cell lung cancer (NSCLC). First, we confirmed this special form of vasculature in NSCLC tissues and found the existence of VM channels in tumor tissues was correlated with Sema4D expression. Further, we found that inhibition of Sema4D in the human NSCLC cells H1299 and HCC827 reduces VM formation both in vitro and in vivo . Moreover, we demonstrated that downregulating the expression of plexinB1 by siRNA expressing vectors and inhibiting the RhoA/ROCK signaling pathway using fasudil can reduce VM formation of H1299 and HCC827 cells. Finally, we found that suppression of Sema4D leads to less stress fibers and depleted the motility of H1299 and HCC827 cells. Collectively, our study implicates Sema4D plays an important role in the process of VM formation in NSCLC through activating the RhoA/ROCK pathway and regulating tumor cell plasticity and migration. Modulation of the Sema4D/plexinB1 and downstream RhoA/ROCK pathway may prevent the tumor blood supply through the VM pattern, which may eventually halt growth and metastasis of NSCLC. Abstract : What's new? Despite the presence of rich vascular supply, anti‐angiogenesis therapy has low efficacy in non‐small cell lung cancers (NSCLCs). Vasculogenic mimicry (VM), the formation of vascular networks composed of aggressive cancer cells, may be one of the reasons. our study explored the effects of sema4D and its downstream RhoA/ROCK signaling pathway, which play an instrumental role in tumor angiogenesis, on tumor VM. Sema4D overexpression and consequential activation of the RhoA/ROCK pathway were linked with tumor cell plasticity and VM formation in NSCLC. Targeting both angiogenesis and vasculogenic mimicry through blocking sema4D and RhoA/ROCK signaling pathway may provide an alternative cancer treatment.